Strategy for the Future of Health - Bushko, Renata G. (IOS Press, 2013)
Bringing together some of the strongest and most advanced voices in the field of medicine and technology, Strategy for the Future of Health examines the constantly changing horizon of ideas and technologies which must be addressed by decision makers involved in health-related resource allocation. Future progress and the provision of long-term solutions in healthcare and medicine depend on the decisions to invest in research, development and education today. This book touches upon all aspects of the system and is rich and diverse enough to provide direction in goal formation for those concerned in making such decisions. Strategy for the Future of Health addresses the unprecedented technological revolution in healthcare which is manifesting itself in the convergence of molecular biology, computer and medical science, electrical, mechanical, genetic and biomedical engineering. Health professionals look towards a future where caring machines will assist them in much of their work and consumers will diagnose and treat themselves with self-health tools, personalized designer drugs and automatic surgery bubbles. Such developments could lead to both dramatic cost reduction and eventually to the delivery of error-free healthcare.